The interaction of marine fouling organisms with topography of varied scale and geometry: a review - Myan, Felicia Wong Yen; Walker, James; Paramor, Odette (American Vacuum Society, 2013)
Many studies have examined the effects of surface topography on the settlement behaviour of marine organisms and this article reviews these investigations with more emphasis on the effects of topography scale. It has been observed that macro topographies (1-100 mm) are generally favoured by marine fouling taxa and are unsuitable for antifouling applications. This is because macro topographies are usually large enough to fit fouling organisms and provide refuge from dangers in the marine environment. Micro topographies had only limited success at reducing fouling from a wide range of marine taxa. The antifouling performance of micro topographies (1 to ≤1000 μm) is dependent on the properties of topography features in terms of symmetry, isotropy, width, length, height/depth, separation distance and average roughness. In terms of the antifouling performance of micro topography, topography geometry may only be of secondary importance in comparison to the size of features itself. It is also noted that hydrodynamic stresses also contribute to the settlement trends of foulers on textured surfaces. Future studies on antifouling topographies should be directed to hierarchical topographies because the mixed topography scales might potentially reduce fouling by both micro and macro organisms. Patterned nano-topographies (1- ≤1000 nm) should also be explored because the antifouling mechanisms of these topographies are not yet clear.